THE ELEMENTS OF RETAIL STORE INTERIOR DESIGN : A QUALITATIVE STUDY ON ENHANCING CUSTOMER IN STORE EXPERIENCE - Minerva, Isaura; Kusumowidagdo, Astrid (Universitas Ciputra Surabaya, 2024)
This research aimed to formulate the essential elements in retail store interior design. The retail store landscape is expected to undergo significant changes and trends in 2024. In this context, digitalization is expected to grow directly in proportion to e-commerce. Several AI-related concepts are also becoming increasingly favored. There are opportunities to explore key design elements in adapting to these developments. A good understanding of these elements can enhance the store’s image and create a positive experience. A qualitative method was also used to obtain 10 participants through focus group discussions involving retail store visitors as well as experts and interior product designers. The results showed that there are several important elements in designing retail store interiors, including physical elements such as the exterior area, interior area, display area, interior layout, and point of purchase. These physical elements play a significant role in creating an attractive and functional store appearance. Additionally, social elements are also important, including merchant characteristics, merchant outfits, crowding, customer characteristics, and privacy. These elements help in creating symbols and meanings relevant to visitors. Therefore, retail interior design that considers the store exterior, store interior, interior layout, and store displays can create a pleasant and meaningful shopping experience for customers